Extracellular Vesicles in Bone Tumors: How to Seed in the Surroundings Molecular Information for Malignant Transformation and Progression - Cappariello, Alfredo; Rucci, Nadia (Frontiers in Oncology, 2021)
Bone is a very dynamic tissue hosting different cell types, whose functions are fine-tuned regulated thank to a plethora of membrane-bounded and soluble molecules, allowing a selective cell-to-cell communication. One of the most spotlighted players of intercellular communications is represented by extracellular vesicles (EVs). These are cell-derived complex structures, ranging from 20 to 1000 nm, able to shuttle biologically active molecules, such as nucleic acids and proteins. The bone microenvironment is a preferential site of primary and metastatic tumors, in which cancer cells find a fertile soil to “seed and blossom”. Nowadays many oncogenic processes are recognized to be sustained by EVs. For example, EVs account for the direct fueling of the vicious cycle in the bone/bone marrow microenvironment, shuttling molecules able to affect the osteoblasts, osteoclasts, osteocytes, adipocytes, leukocytes and endothelial cells, creating a comfortable environment for tumor growth. Parallelly, other crucial tumor-mediated events, such as the premetastatic niche formation, tumor cell dormancy as well as drug resistance, have been described to be fostered by tumor-derived EVs. In this review, we will resume the main body of literature describing how the cancer cells use the EVs for educating the bone microenvironment for an adequate homing and long-term colonization into the bone.